Uniform Pricing as a Barrier to Entry. (4th April 2023) - Feng, Hong; Li, Youping; Shuai, Jie
Abstract : This paper considers an entry game in which an incumbent firm operates in a number of markets and a potential entrant can enter multiple or all of the markets. While price discrimination has usually been thought of as a barrier to entry, in our model it is not and instead, charging a uniform price across the markets can discourage entry. Partial entry occurs when the two firms' products are highly substitutable. In this case, uniform pricing raises the profits of both the incumbent and the entrant but reduces consumer and total welfare relative to price discrimination.